2004
DOI: 10.1111/j.1467-8691.2004.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Project Factors Influencing Conflict Intensity and Handling Styles in Collaborative NPD

Abstract: Conflict and conflict management are critical research issues in client-supplier collaborative new product development (NPD). A recent study found that conflict intensity and conflicthandling styles affect collaborative NPD performance. In this paper, we explore the relationships of four NPD project factors, namely product technical complexity, product certainty, task interdependence and the relative power of supplier, to conflict intensity and suppliers' adoption of integrating and dominating conflict-handlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Most modern work roles demand some form of reciprocal interaction with others to accomplish work goals. Research findings on the effects of task interdependence have been mixed, some suggesting positive outcomes (e.g., Lam and Chin 2004;Gundlach et al 2006), whereas others suggesting that it leads to negatives outcomes, such as conflict (e.g., Xie et al 1998). It will be interesting to see whether the negative effects of task interdependence will be more evident in the case of individuals with low calling, who might feel burdened by the higher consensual requirements within strong interdependent contexts.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 96%
“…Most modern work roles demand some form of reciprocal interaction with others to accomplish work goals. Research findings on the effects of task interdependence have been mixed, some suggesting positive outcomes (e.g., Lam and Chin 2004;Gundlach et al 2006), whereas others suggesting that it leads to negatives outcomes, such as conflict (e.g., Xie et al 1998). It will be interesting to see whether the negative effects of task interdependence will be more evident in the case of individuals with low calling, who might feel burdened by the higher consensual requirements within strong interdependent contexts.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 96%
“…Research (e.g., Schopler, 1986) has shown that when organizational teams share resources (high task interdependence), competitive strategies may be used to acquire maximum resources and power. Others, however, have stated that although high task interdependence increases the amount of interaction among members, it provides an incentive for collaboration (Lam & Chin, 2004). When task interdependence is high, team members typically communicate more often, are closer physically, and support and influence each other regularly.…”
Section: The Effect Of Task Interdependencementioning
confidence: 99%
“…Perceived task interdependence within the organization was assessed with a scale by Bishop and Scott (; five items; α = .86; the scale was translated and back‐translated from English to German by individuals fluent in both languages). Perceived task interdependence (i.e., “the extent to which employees perceive that their tasks depend on interactions with others and on others’ tasks being completed”; Bishop & Scott, , p. 440) was included because task interdependence creates opportunities for conflict especially when incompatibilities arise (e.g., Jehn, ; Saavedra, Earley, & Van Dyne, ; Somech et al., ) but also can create an incentive for collaboration and cooperation (Lam & Chin, ). The type of an organization (e.g., profit vs. nonprofit) was included, as research has shown that it relates to perceptions of conflict.…”
Section: Methodsmentioning
confidence: 99%